Modeling the Influence of Surface Free Energy on Moisture Damage of Recycled Asphalt Concrete - Saad Issa Sarsam; Rana Khalid Hamdan (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Recycling is a sustainable process for restoration of the pavement quality. In this investigation, aged binder was recycled by digestion with (0.5, 1.0, and 1.5) % of polyethylene and crumb rubber. The recycled binder was implemented in the preparation of Marshal specimens. The surface free energy of the control and recycled binder was determined using the Sessile drop method. Specimens were tested under repeated indirect tensile and double punching shear stresses with the aid of pneumatic repeated load system (PRLS). Another group of specimens was tested for moisture damage, then subjected to the same loading sequence. Specimens were subjected to 1200 load repetitions under stress level of 0.138 MPa at 25 °C. The load was sustained for 0.1 second followed by 0.9 seconds of rest period. The permanent deformation was measured before and after moisture damage process for each testing technique. Regression analysis is used to develop a model for the influence of surface free energy on the deformation and the moisture damage using the SPSS Software. It was concluded that the obtained model can explain 82 % of the variation in moisture damage due to the influence of surface free energy.